Attaining near-theoretical densification in nanograined pyrochlore La2Zr2O7 (LZ) ceramic at 1150 °C by spark plasma sintering. (May 2016) - Kumar, Rishu; Singh, Kushal; Chakravarty, Dibyendu; Chowdhury, Anirban
Abstract: Phase-pure Lanthanum zirconate nanopowders (La2 Zr2 O7, LZ) were synthesized by co-precipitation method and subjected to densification studies. No additive/sintering aid was used, neither was any slurry processing performed to improve the quality of the powders. LZ ceramic with near-theoretical density (> 98%) was obtained at 1150 °C by spark plasma sintering; the lowest sintering temperature reported till date. The LZ ceramic comprised of small equiaxed grains ( 300 nm) and recorded a significant improvement in hardness ( 14 GPa) and scratch resistance measured by nanoindentation. The study clarifies that all previous reports involving poor sinterability of LZ system was related to inferior quality precursors. Graphical abstract: